Analisis turbulensi pada pesawat Etihad Airways EY-474 tanggal 4 Mei 2016 dengan metode Weather Research and Forecasting - Nuriyana Muthia Sani; Rahmat Gernowo (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
The micro weather analysis for turbulence incident of EY-474 Eithad Airways aircraft on May 4, 2016 involving injured passengers, was numerically simulated using the Weather Research and Forecasting (WRF) numerical model software. The input data is obtained from the predicted Final Analysis (FNL) that can be downloaded at the site. Elements obtained from WRF output include Richardson Number Index (Ri) and Vertical Wind Shear (VWS). Flight data to determine the time and location of the turbulence events obtained from the site address. The results obtained events around the waters of Palembang and Bangka Island. And supported by Himawari 8 satellite image data infrared (IR) canal and visible canal (VIS) and Kochi University infrared (IR) satellite to see the condition of the clouds. The results of the Kochi University satellite data show there are no convective clouds. However, on the Himawari 8 satellite shows there are clouds with peak temperatures cool enough and showing a central cloud. Simulation results show turbulence with strong intensity explaining turbulence incident on May 4, 2016 in Palembang and Bangka Island waters. Keywords: himawari, turbulence, WRF